2002
DOI: 10.1093/bja/88.6.841
|View full text |Cite
|
Sign up to set email alerts
|

Dopexamine attenuates microvascular perfusion injury of the small bowel in pigs induced by extracorporeal circulation

Abstract: Our data demonstrate that treatment with the vasoactive drug dopexamine leads to a significant reduction of the perfusion injury of the small bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…However, this would result in a baroreflex-mediated increase in HR, which again we did not observe. Nevertheless, blood flow may still be redistributed within the different organ systems, equating to no overall change, which is supported by studies in rats (Yeh et al 2012), but conflicted by several studies in pigs (Schwarz et al 2001;Sack et al 2002;Hiltebrand et al 2011). This finding might have been confounded by the slight variation in isoflurane percentages needed to maintain surgical levels of anesthesia across groups; although the lack of response differentiation between nondiabetic and diabetic animals suggests this is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…However, this would result in a baroreflex-mediated increase in HR, which again we did not observe. Nevertheless, blood flow may still be redistributed within the different organ systems, equating to no overall change, which is supported by studies in rats (Yeh et al 2012), but conflicted by several studies in pigs (Schwarz et al 2001;Sack et al 2002;Hiltebrand et al 2011). This finding might have been confounded by the slight variation in isoflurane percentages needed to maintain surgical levels of anesthesia across groups; although the lack of response differentiation between nondiabetic and diabetic animals suggests this is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the excess systemic and gut mucosal lactate production seen during CPB may result from an inflammatory effect causing mitochondrial dysfunction. Regional impairment and redistribution of blood flow within the layers of the gut wall during CPB may also be a contributing factor to local lactate production [35]. Others have suggested that increased production of lactate in the gut tissue contributes to increased systemic lactate concentrations in CPB patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies underline that microcirculation and/or tissue oxygenation are impaired during cardiac surgery. This impairment appears to be transient and resolves early in the postoperative hours.…”
mentioning
confidence: 99%